USAGE OF YOU TUBE- BASED VIDEOS IN LEARNING DAILY ENGLISH CONVERSATION FOR CHILDREN AT ASRAMA YATIM MIZAN AMANAH, SALIHARA, PASAR MINGGU, SOUTH JAKARTA - Evi Jovita Putri; Gilang Ilham Agustinus; Intan Kusuma Wardhani (Universitas Nasional, 2020)
ABSTRACT This research aims to analyze the effectiveness of YouTube-based videos as a media in learning daily English conversation for children and to identify factors affecting learning daily English conversation for children by using YouTube-based videos as a media. To obtain the aims, this research uses six children whose ages vary from ten to twelve years old lived in Asrama Yatim Mizan Amanah located at Jalan Salihara, Pasar Minggu, South Jakarta as the source of data. Descriptive qualitative method is applied as the research design. In collecting data, the researchers gather the result of learning activities in pre-tests, treatments, and post-tests. Meanwhile, in analyzing the data, the researchers compare the children’s pre-test score with their post-test score to see the development of learning which show their competence before and after being treated. in this case, the research is focused on two topics, Greeting and Introduction in English. The children are introduced some expressions of greeting and introduction in English children by using YouTube-based videos, then some roleplays or conversation containing expressions of greeting and introduction are shown to the children by watching together YouTube-based videos. The last, the children are asked to recognize and practice the expression of greeting and introduction in English. The result shows that the usage of YouTube based video as a media in learning daily English conversation for children is considered effective. Four out of six children are able to memorize new expressions of both greeting and introduction in English, whereas the two other children remains stagnant after learning using YouTube based videos. It is found that there are factors that affect learning English for children by using this media, they are; personality, motivation and attitude, intelligent, learners’ belief, and personality. The most influential factors affecting learning are motivation and attitude. The successful children have these factors stronger rather than the stagnant children. Based on the result, the effectiveness in learning English using YouTube-based videos will be stronger if it is supported by an interactive and conducive learning atmosphere. The learning atmosphere should be considered to achieve a stronger speaking English proficiency. Key words: YouTube based-videos, language learning, daily English conversation ABSTRAK Penelitian ini ditujukan untuk menganalisis keefektifan penggunaan video berbasis YouTube sebagai media dalam belajar percakapan bahasa Inggris sehari-hari pada anak-anak dan untuk mengidentifikasi faktor yang mempengaruhi pembelajaran percakapan bahasa Inggris sehari-hari pada anak-anak yang menggunakan video berbasis YouTube. Untuk mencapai tujuan tersebut, penelitian ini menjadikan enam orang anak berumur sepuluh hingga dua belas tahun yang tinggal di Asrama Yatim Mizan Amanah Jalan Salihara, Pasar Minggu, Jakarta Selatan sebagai sumber data. Penelitian ini menggunakan metode descriptive qualitative. Disini, proses pengumpulan data meliputi pengumpulan hasil pre-tests, treatment, dan post-test. Sementara itu, proses analisis data dilakukan dengan cara membandingkan skor pre-test dengan skor post-test pembelajar untuk melihat perkembangan pembelajaran yang menunjukkan perkembangan anak-anak sebelum dan sesudah pembelajaran. Penelitian difokuskan pada dua topik pembelajaran yaitu sapaan dan perkenalan bahasa Inggris. Dalam hal ini anak-anak diajak mengenal ekspresi sapaan dan perkenalan dalam Bahasa Inggris melalui video yang ada pada YouTube. Kemudian menonton beberapa simulasi dari perilaku menyapa dan berkenalan dalam Bahasa Inggris juga melalui video You-Tube. Pada tahap terakhir, para pembelajar ini diminta untuk berlatih mengingat dan mempraktekkan ungkapan sapaan dan perkenalan dalam Bahasa Inggris Hasil penelitian menunjukkan bahwa penggunaan video berbasis YouTube sebagai media belajar percakapan bahasa Inggris sehari-hari adalah efektif. Empat dari 6 anak mampu mengingat kosakata sapaan dan perkenalan yang baru secara signifikan setelah belajar menggunakan media video berbasis You Tube, meskipun ada 2 anak yang tidak mengalami peningkatan. Ada beberapa faktor yang memengaruhi pembelajaran pada anak-anak tersebut diantaranya kepribadian, motivasi dan sikap, kecerdasan, dan keyakinan. Faktor yang paling berpengaruh pada pembelajaran adalah motivasi dan sikap. Anak-anak yang mengalami peningkatan belajar yang pesat memiliki faktor motivasi dan sikap yang lebih kuat dibanding anak-anak yang tidak mengalami peningkatan. Berdasarkan hasil tersebut, keefektifan dalam belajar percakapan Bahasa Inggris sehari-hari menggunakan video YouTube menjadi lebih besar jika didukung oleh atmosfer belajar yang interaktif dan kondusif. Hal ini mesti diperhatikan guna mencapai kemampuan Bahasa Inggris lisan yang lebih baik. Kata Kunci: Video YouTube, Pembelajaran Bahasa, Percakapan dasar dalam Bahasa Inggris.